THE â€œUNJUST ENRICHMENTâ€ IN INTELLECTUAL PROPERTY RIGHTS: A PROPHETIC LEGAL PARADIGM - Made Jayantara; I Gede Agus Kurniawan; Putu Aras Samsithawrati (Jurnal Pembaharuan Hukum, 2023)
The purpose of this study is to analyze the implications of the concept of Unjust Enrichment in the realm of intellectual property rights and the orientation of the application of the concept of Unjust Enrichment in the realm of intellectual property rights from a prophetic law perspective. This research is a normative legal research using a case, concept, and statutory approach. The results of the study state that the implication of the concept of Unjust Enrichment in the realm of intellectual property rights is intended to protect creators of works or holders of intellectual property rights, especially in fulfilling economic rights. The orientation of the application of the concept of Unjust Enrichment in the realm of intellectual property rights in the perspective of prophetic law is that the Supreme Court Decision which becomes jurisprudence must be a guide and guide for judges in resolving cases related to Unjust Enrichment in the realm of intellectual property rights. The main finding in this study is that three aspects of prophetic law, namely liberation, humanization, and transcendence are three aspects that must be met and considered in the application of the concept of Unjust Enrichment in all rules related to intellectual property rights, including the formulation of sanctions as well as legal remedies that can be taken if there is a loss suffered by the holder of intellectual property rights.